A systematic review of the literature addressing asepsis in wound management - Haesler, E.; Thomas, L.; Morey, Pamela; Barker, J. (Cambridge Publishing, 2016)
There has been extensive ongoing debate on the application of aseptic technique in wound management over the previous decades and changes to the way in which theory is applied to clinical practice have occurred regularly. Clinicians often express confusion over the way various techniques should be applied, particularly when practising in clinical settings in which maintenance of strict asepsis is inherently difficult (for example, community-based wound management). Wound cleansing, use of open but unused wound dressings and storage of wound management equipment are frequent issues on which clinicians request guidance. A systematic review using Joanna Briggs Institute methods was undertaken in order to establish the current state of the scientific literature on this topic and inform the development of recommendations for practice in this field. All levels of evidence were included in the review, including opinion papers. Findings from the 20 quantitative studies were reported in narrative summary and findings from 37 qualitative research papers were aggregated in a thematic synthesis. Although high-level evidence on wound cleansing solutions was identified, the review concluded that there is a paucity of scientific literature on most topics related to asepsis in wound care.